Analisis Kepadatan Penduduk terhadap Perubahan Tutupan Vegetasi Menggunakan NDVI di Kecamatan Medan Tuntungan - Nababan, Yolanda; Marbun, Sahala Fransiskus; Sitompul, Ryan Lucky Sartua; Simanjuntak, Joy Any Hasian; Hulu, Selfianus (PT. Intelek Cendikiawan Nusantara, 2025)
Population growth in peri-urban areas is increasingly recognized as a major driver of land-use change, particularly through the reduction of vegetation cover. This study examines the dynamics of vegetation change using NDVI analysis alongside the development of population density in Medan Tuntungan District between 2014 and 2023. The analysis draws on Landsat 8 imagery and sub-district-level demographic data. The findings reveal a substantial decline in areas classified as high to very high vegetation density, amounting to approximately 411 hectares. Conversely, areas categorized as low to very low NDVI expanded by around 305 hectares over the same nine-year period. During this interval, the population increased from 84,775 to 99,184 inhabitants, reflecting a growth of roughly 17%. Kelurahan with the highest population increases such as Simpang Selayang, Simalingkar B, and Tanjung Selamat displayed the most pronounced vegetation loss. These results indicate intensifying pressure on vegetation as population density rises, leading to the expansion of low-vegetation areas due to land conversion for residential and urban infrastructure development. Overall, the study underscores the urgency of strengthening spatial planning control and protecting green open spaces to maintain ecological sustainability in the peri-urban zones of Medan